Land-Use Planning and the Urban Heat Island. (December 2014) - Kim, Jun-Pill; Guldmann, Jean-Michel
Local-climate changes due to urbanization are epitomiz ed by the urban heat island (UHI), which is characterized by temperature differences between urban and rural areas. The UHI is a critical factor for energy consumption and air quality, resulting in higher peak electricity demand in summer because of air conditioning, increased emissions of primary pollutants associated with power production, and increased generation of ozone. However, planners need a better understanding of the relationship between the UHI and land-use patterns in order to reduce the UHI and promote more sustainable urban development. This research develops statistical models of local surface temperatures, using Landsat-5 satellite remote-sensing data, whereby the temperature at any location and for any land use is modeled as a function of the pattern of land uses around this location. Normalized Difference Vegetation Index (NDVI) and area land-use variables are used as inputs to these models, which are estimated with data for the Columbus, Ohio, metropolitan area. The results confirm the effects of neighboring land uses on local temperatures. The applicability of these models for land-use planning is illustrated by simulating hypothetical land-use changes, and computing the resulting temperature effects. The results demonstrate that it is possible to reduce temperatures in residential and urban areas through judicious siting of green areas.